A Business Typology for Luxury Consumption in an Inconspicuous Way: A Proposed Model - Ting, Mao Seng; Goh, Yen Nee; Isa, Salmi Mohd (Journal of Entrepreneurship, Business and Economics; Vol 9 No 2 (2021), 2021)
To date, luxury consumption-related research has primarily focused on conspicuous consumption and counterfeit consumption behaviour. Investigation into the influence of inconspicuous consumption behaviour is limited. This study explores the factors that influence consumers’ purchase intention towards subtle luxury fashion goods or inconspicuous consumption behaviour. This paper examines a Triandis model that clarifies the consumers' purchase intention of subtle luxury fashion goods. A systematic literature review was used to conduct a database search. Articles published from 2010 to 2020 were considered, and 49 studies were key factors influencing consumers’ inconspicuous consumption behaviour. This review highlights how consumers’ inconspicuous luxury consumption is based on attitudinal, social, and affective factors. Furthermore, two moderators, namely perceived knowledge and habit, were identified. These moderators might close the relationship gap between consumers' purchase intention of subtle luxury fashion products and their actual buying behaviour to these subtle products. This paper may encourage future scholars to study inconspicuous consumption-related studies. Furthermore, this paper may have practical implications that may benefit luxury marketers, luxury owners, and luxury retailers. Research paper Keywords: Inconspicuous consumption; Triandis model; Theory of Interpersonal Behaviour; Subtle luxury fashion products; purchase intention Reference to this paper should be made as follows: Ting, M. S., Goh, Y. N., & Isa, S. M. (2021). A Business Typology for Luxury Consumption in an Inconspicuous Way: A Proposed Model. Journal of Entrepreneurship, Business and Economics , 9 (2), 1–38.